Chemical profiling of two aromatic weeds, Cyathocline purpurea and Blumea lacera - Mokat, Digambar Nabhu; Torawane, Sarika Daulatrao; Suryawanshi, Yogesh Chandrakant (Current Botany, 2020)
In the present investigation chemical constituents of Cyathocline purpurea (Buch.-Ham. ex D.Don) Kuntze and Blumea lacera (Burm.f.) DC. (Family-Compositae) were studied by using gas chromatography coupled with mass spectrometry (GC/MS). These two weeds are small herbs and well known for its potent medicinal properties. Total 17 and 27 compounds were identified from C. purpurea and B. lacera respectively. The major constituents in both the extracts were pentadecanoic acid, 14-methyl-, methyl ester (30.56 %), cis-phytol (21.26 %), α- cadinol (7.87 %), γ-cadinene (7.13 %), neophytadiene (3.81 %) and α-cubebene (1.82 %). GC/MS analysis revealed the presence of various bioactive compounds such as fatty acids, sesquiterpenoids, phenols, etc. in the acetone extracts of both the plants. The identified compounds have various biological activities.